O lúdico e a geografia: a produção acadêmica brasileira sobre o jogo no séc. XXI - Santos, Joanna Luísa Barros dos (2024)
knowledge and practices, theories and methodologies, and the history of school and academic geography. In this thematic universe, Playful Education and game-based learning appear as an alternative to renew and diversify Geography teaching methods, approached from both the methodological sphere and teaching resources. The theme of this research is directly related to Geography, as it analyzes the academic production that combines Playful Education with Geographic Education throughout the first two decades of the current century, through games. This bibliographical research, of a quantitative nature, had the general objective of mapping theses and dissertations produced in Brazil from 2001 to 2020, focusing on the discussion about Playful Education through games related to Geography. The specific objectives involved the review of theories and concepts, contextualization of the period and the analysis of elements of the texts collected. Using review procedures in theoretical and conceptual references, together with a systematic mapping in theses and dissertations, the research revealed an increasing volume of texts in the second decade of the period, with 2019 being the most prolific year in publications. The geographical distribution of the works showed a predominance in the Southeast-South axis, with an absence of documents for the North region. The keywords highlighted the connection with Geography, cartography, technologies and teaching, reflecting a multifaceted interpretation of the game. As for the approach profiles, the most recurrent were theoretical reflection, game creation, report of game use and game evaluation, with the majority of documents characterized by mixed profiles with more than one approach. These results provide a comprehensive understanding of academic production on Ludic Education and games related to Geography in the Brazilian context.